Mother's Day murder : a Lucy Stone mystery - Meier, Leslie (Meier, Leslie. Lucy Stone mystery., 2009)
Reporter Lucy Stone, of Tinker's Cove, Maine, uncovers some icky revelations about Bart Hume, a philandering cardiac surgeon, as she investigates a shooting murder connected to a suspicious accident fatality and the disappearance of a teen youth counselor. Along the way, Lucy and Sara, Lucy's high school freshman daughter, are caught in a deadly game of cat and mouse with the killer.